Features of the Cognitive Approach in Forecasting Systems of Staff Training for the Real Sector of the Russian Economy. (17th October 2015) - Gorbachev, Sergey; Syryamkin, Maksim; Syryamkin, Vladimir; Vaganova, Elena
Abstract: The authors reveal aspects of their research, the purpose of which is to improve the socio-economic development of the country. Based on the forecast, the advanced training of specialists in the field of analysis of the various sectors of the Russian economy, as well as in the management of state innovation infrastructure are considered.